Degenerated (p, q)-Laplacian With Weights and Related Equations With Convection. (18th November 2021) - Motreanu, D.; Nashed, M. Z.
Abstract: We consider Dirichlet boundary value problem where the elliptic equation is driven by a ( p, q )-Laplacian with weights and that contains a convection term (i.e., it depends on the solution and its gradient). The notion of ( p, q )-Laplacian with weights is considered for the first time. We present an existence result whose proof is based on the theory of pseudomonotone operators. An example illustrates its applicability.